2022
DOI: 10.3389/fpsyg.2022.935209
|View full text |Cite
|
Sign up to set email alerts
|

Understanding individual and collective response to climate change: The role of a self-other mismatch

Abstract: Several scientists have shown the importance of mitigating global warming and have highlighted a need for major social change, particularly when it comes to meat consumption and collective engagement. In the present study (N = 486), we conducted a cross-sectional study to test the mismatch model, which aims at explaining what motivates individuals to participate in normative change. This model stipulates that perceiving a self—other difference in pro-environmental attitudes is the starting point and can motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Based literature on veg*ns’ main motives and collective goals ( MacInnis and Hodson, 2021 ; De Groeve and Rosenfeld, 2022 ), we presuppose that veg*n advocacy primarily involves claims that animal-product consumption harms animals, while claims about environmental and/or health harms are secondary. Stronger moral convictions, a stronger rejection of carnist and speciesist majority beliefs and a higher perceived inconsistency between moral vs. majority beliefs may motivate activism ( Piazza et al, 2015 ; Harrington et al, 2022 ). In addition, Judge et al (2022) showed that more principled convictions predict engagement in vegan advocacy via a stronger identification with other vegans and animals, perceived collective efficacy and moral outrage.…”
Section: Theoretical Accountmentioning
confidence: 99%
“…Based literature on veg*ns’ main motives and collective goals ( MacInnis and Hodson, 2021 ; De Groeve and Rosenfeld, 2022 ), we presuppose that veg*n advocacy primarily involves claims that animal-product consumption harms animals, while claims about environmental and/or health harms are secondary. Stronger moral convictions, a stronger rejection of carnist and speciesist majority beliefs and a higher perceived inconsistency between moral vs. majority beliefs may motivate activism ( Piazza et al, 2015 ; Harrington et al, 2022 ). In addition, Judge et al (2022) showed that more principled convictions predict engagement in vegan advocacy via a stronger identification with other vegans and animals, perceived collective efficacy and moral outrage.…”
Section: Theoretical Accountmentioning
confidence: 99%